Valuing Native American tribal elders and stories for sustainability study. Issue 2 (14th March 2016) - Gritter, Kristine; Scheurerman, Richard; Strong, Cindy; Schuster, Carrie Jim; Williams, Tracy
Abstract: This article outlines a framework the authors have used to infuse sustainability study into humanities teaching at the middle school level. Native American tribal elders can act as co-teachers in such classrooms, and the place-based stories that shaped their views of the environment can serve as important classroom texts to investigate sustainable philosophies. Middle school students can learn to read with a sustainable lens and learn to use the narrative wisdom of tribal elders to read across texts for sustainability themes and messages. Respect for Native American culture flourishes in such an environment. Examples of Native American storied resources for sustainability are offered in this article.